Nigerian youth: victims of the 21st century - Dahiru, Suleiman; Ahmad, Nobaya; Jaafar, Wan Munira (Elixir International Journal, 2016)
The article focuses on the Nigerian Youths as Victims of this 21st century, as it is believed that they are the leaders, movers, propellers of the socio economic, political and intellectual development of every nation. The youth have fallen victims of the danger of social problems ie poverty, violence, use of arms and a new face of immorality such as baby factory phenomenon etc to survive. What is the hope of the Nigerian youths in the 21st century is one of the questions raised. Anomie theory was use to explore the Nigerian Youths as victims of the 21st century.